On the definition of differential reinforcement of alternative behavior. Issue 3 (20th March 2020) - Vollmer, Timothy R.; Peters, Kerri P.; Kronfli, Faris R.; Lloveras, Lindsay A.; Ibañez, Vivian F.
Abstract : Differential reinforcement of alternative behavior (DRA) has a long history as a behavioral treatment. The term has usually been defined in a manner that suggests one form of behavior (usually some appropriate alternative) is reinforced, while another form of behavior (usually problem behavior) is placed on extinction. In this paper, we will suggest that DRA should not require extinction, either procedurally or by definition. Ideally, problem behavior would be placed on extinction when possible; however, when problem behavior is not or cannot be placed on extinction, the procedure used is still DRA. Thus, we propose the following definition: Providing greater reinforcement, along at least one dimension, contingent on the occurrence of one form or type of behavior, while minimizing reinforcement for another form or type of behavior.